MODEL PENDAMPINGAN TERINTEGRASI BLK-KOMUNITAS MENUJU INKUBATOR KEWIRAUSAHAAN - Ahmad Muttaqin; Mawi Khusni Albar (Jurnal Ilmiah Mahasiswa Raushan Fikr, 2025)
Integrated assistance within BLK-Community programs aimed at fostering entrepreneurial incubators plays a vital role in producing competent and highly competitive entrepreneurs. Such comprehensive mentoring, involving collaboration across various stakeholders—academics, practitioners, and the industrial sector—offers participants essential access to resources, including mentorship, business networks, and funding opportunities. This research adopts a qualitative approach. The findings reveal: 1) BLK-Community Region III at UIN Prof. K.H. Saifuddin Zuhri Purwokerto serves as an educational and training institution dedicated to empowering communities by enhancing entrepreneurial skills and knowledge; 2) The implementation of the Integrated Mentoring Model within BLK-Community Region III is aimed at developing a supportive entrepreneurial ecosystem through a holistic approach, encompassing technical, managerial, and marketing skills training. This model integrates various mentoring elements, such as guidance from experienced practitioners, project-based learning, and access to business networks, enabling participants to acquire firsthand insights from industry best practices. 3) Several significant challenges persist, including a shortage of qualified human resources, insufficient infrastructure, and limited access to business capital. Additionally, inadequate support from the private sector and government, coupled with the rapid evolution of market dynamics, further complicate the challenges that need to be addressed